Constitutionality of The Omnibus Law Number 11 of 2020 on Job Creation - Marpaung, Jessica Vincentia; Utama, Gwendolyn Ingrid; Hermawan, Florence (Dialogia Iuridica, 2023)
The concept of “Omnibus Law” has been a topic of controversy in Indonesia from the moment it was proposed by President Joko Widodo to date. Throughout 2020, out of the 50 draft laws to be prioritized in the National Legislation Program, the Job Creation Draft was undeniably the most discussed and disputed. Debates revolved around not only the material content of the draft law (among others, the potential yet dilemmatic revocations or amendments of other laws and legislations resulting from the enactment of such cross-sectoral law), but also the procedural soundness of its legislative process (among others, the issues of transparency and representation in the legislative drafting process). These debates point towards not only the constitutionality of “Omnibus Law”, but also the political will of the law itself – aspects that were all the more pressing to be scrutinized as the Government moved on crystalize the Job Creation Draft Omnibus Law into a positive law, namely Law Number 11 of 2020 on Job Creation. This research will investigate three indispensable aspects. First, investigate into the constitutionality and resulting enforceability of Job Creation Law. Second, dissect relevant aspects of said Omnibus Law and determine its impacts to applicable laws and legislations. Third, eventually venture to utilize all the mentioned analysis, synthesize a conclusive observation of Job Creation Law. Other than establishing the said analysis, this research will hopefully provide a set of indications of how the Job Creation Law, and in turn, Omnibus Law in general, will be enforced in Indonesia.